Impact of digital health interventions on quality of life and mental health in older adults with chronic diseases: a systematic review and meta-analysis - Hu, Enliang; Wang, Haozhe; Yao, Jiayi; Liao, Mingyu; Chen, Wenjia (Frontiers in Aging, 2026)
BackgroundChronic diseases significantly impact the health of older adults globally. While digital health technologies offer new avenues for management, existing evidence remains inconsistent with methodological limitations.MethodsWe systematically searched eight databases, including PubMed and Web of Science (from inception to 31 July 2025), for randomized controlled trials (RCTs) involving patients aged 60 and above with chronic conditions. A random-effects model was used to synthesize data to evaluate the impact of digital health interventions on general quality of life (QoL), disease-specific QoL, and mental health. The quality of evidence was assessed using the GRADE system.ResultsFifteen RCTs (n = 3253) were included. The meta-analysis showed that digital health interventions significantly improved general QoL (SMD = 0.54, 95% CI [0.30, 0.78]), disease-specific QoL (SMD = 0.39, 95% CI [0.17, 0.60]), and mental health status (SMD = 0.36, 95% CI [0.22, 0.50]) in older adults with chronic diseases. Although heterogeneity was observed in some outcomes, sensitivity analyses confirmed the robustness of the results. The GRADE assessment indicated that the quality of evidence for mental health improvement was high.ConclusionDigital health interventions effectively enhance the quality of life and mental health of older adults with chronic diseases, demonstrating clear clinical significance. The evidence supports the integration of digital health technologies into routine care systems, particularly standardized interventions for patients with respiratory and metabolic diseases.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251107861, identifier CRD420251107861.